Effects of habitat age and disturbance intensity on the biodiversity of three trophic levels in Central Kenya. (14th March 2016) - Eisenring, Michael; Beck, Jan; Agwanda, Bernard; Kioko, Esther; Curran, Michael
Abstract: In recent decades, the extent of primary forest in tropical regions has decreased drastically, with concurrent increases in the extent of tropical secondary forest. This has important implications for conservation management. We present novel data on species diversity and composition for three taxa (bats, geometrid moths and plants) in forests at two stages of secondary growth located in the Aberdare Mountains in Central Kenya. We found no significant differences in alpha diversity for any of the sampled groups between forest types. However, we found disturbance‐driven differences of tree and herb community compositions and correlations between tree and moth – and tree and shrub community compositions. Changes in community compositions were more pronounced using an abundance‐based indicator (Bray–Curtis) in comparison with an incidence based (Sørensen). Our results demonstrate that solely working with alpha diversity values can be misleading in conservation planning as they might not reflect compositional changes between habitats. Furthermore, abundance‐based compositional measures appear to be superior to incidence‐based measures for detecting subtle effects of disturbance on biodiversity.